Penerapan Prinsip Jurnalisme Dalam Film The Post - Monawaroh Aisyah Lestari; Aliasan .; Jufrizal . (CV. ITTC INDONESIA, 2026)
This study is entitled The Application of Journalism Principles in The Post. This research discusses how journalism principles are represented through scenes, dialogues, and characters’ actions in The Post. The background of this study is based on the importance of applying journalism principles in mass media practices, especially in delivering information related to public interest. The Post was chosen because it portrays the struggle of journalists and newspaper editors in revealing the confidential Pentagon Papers amid political pressure, legal threats, and power interests. This study uses a qualitative descriptive method with the semiotic approach of Roland Barthes. The analysis was conducted through three levels of meaning: denotation, connotation, and myth. This research also applies the theory of the nine elements of journalism proposed by Bill Kovach and Tom Rosenstiel as the main analytical framework. The results of the study show that The Post represents various journalism principles, such as obligation to the truth, loyalty to citizens, discipline of verification, independence, monitoring power, providing a public forum, making important issues interesting and relevant, keeping news proportional and comprehensive, and exercising personal conscience. These representations are shown through newsroom activities, editorial decision-making processes, and the courage of journalists in revealing information to the public. The conclusion of this study indicates that The Post functions not only as entertainment media but also as a representation of values, ethics, and social responsibility in journalism practice.